Strategies to Minimize Blood Loss and Transfusion in Pediatric Spine Surgery. Issue 5 (May 2017) - O'Donnell, Courtney; Michael, Nicole; Bloch, Nikki; Erickson, Mark; Garg, Sumeet
Abstract : Definitive correction of pediatric spinal deformities can result in considerable blood loss, operative time, cost, and need for allogenic blood transfusion. Numerous intraoperative strategies are utilized by surgeons and anesthesiologists to minimize blood loss through conservation or transfusion. With the use of modern perioperative blood-conserving techniques, blood loss and blood transfusion rates have been reduced substantially in pediatric patients treated operatively for spinal deformities.